Investigation on the electrical conductivity and tribological properties of NbSe2-doped lubricating grease - Lining Wu; Jie Yan; Zhengfeng Cao; Yanqiu Xia; Hao Wu (Materials Research Express, 2022)
Developing lubricants with good electrical conductivity and good tribological properties is necessary for the power equipment. Here, niobium selenide (NbSe _2 ) and boron nitride (BN) were employed to act as additives to fabricate the lubricating greases with superior electrical conductivity and tribological properties. The lubricating grease containing different concentrations of additives were synthesized and their conductivities were measured by a volume resistance meter at the room temperature of about 25 °C. The tribological properties of the lubricating greases were also investigated and the worn surfaces were characterized in detail by scanning electron microscopy (SEM), x-ray photoelectron spectroscopy (XPS) and Raman spectroscopy to analyze the lubrication mechanism after friction test. The results showed that NbSe _2 could effectively reduce the volume resistivity by ten times as compared with the base grease. Tribological tests showed that when the concentration of NbSe _2 was 2 wt%, it could reduce the COF and wear scar width by 23.5% and 12.8% under 150 N and 5 Hz, indicating 2 wt% NbSe _2 doped lubricating grease exhibited the outstanding tribological properties. In addition, based on the analysis of the wear surfaces, the superior tribological properties of NbSe _2 grease were attributed to the effective lubricating film generated on the friction surface, which played a key role in reducing friction and anti-wear.